ESG Integration and Cost Efficiency Assessment: Evidence from GCC Banking - Aldousari, Abdullah (International Journal of Energy Economics and Policy, 2026)
This research examines the impact of Environmental, Social, and Governance (ESG) factors on cost-efficiency in GCC commercial banks over the period 2018-2022. The analysis employs a two-step Stochastic Frontier Analysis (SFA), followed by panel data Generalized Least Squares (GLS) regression, and covers a sample of 48 banks. Baseline results indicate that environmental and governance factors are associated with higher cost inefficiency, while social factors have no significant effect. Further analysis reveals that social and governance factors become efficiency-enhancing under strong institutions. ESG initiatives increase costs in the short to medium term when ESG scores are low, unless they are strategically integrated into core operations. Inefficiency also arises with higher NPLs, capital reliance and weaker governance during the COVID-19 crisis. This research highlights the context-dependent effects of ESG practices on bank efficiency in the GCC region.